Effects of M2000 (D-Mannuronic Acid) on Learning, Memory Retrieval, and Associated Determinants in a Rat Model of Alzheimer's Disease. (February 2017) - Athari Nik Azm, Somayeh; Vafa, Mohammadreza; Sharifzadeh, Mohammad; Safa, Majid; Barati, Anis; Mirshafiey, Abbas
Thed -mannuronic acid (M2000) is a novel nonsteroidal anti-inflammatory drug that has immunosuppressive effects together with antioxidant property. M2000 has shown a notable efficacy in experimental models of multiple sclerosis, rheumatoid arthritis, and nephrotic syndrome. In this work, the effect of M2000 on the treatment of Alzheimer's disease (AD) was performed by Morris water maze experiment, and the immunological assessments were carried out by Western blot, apoptosis (procaspase-3, Bax/Bcl2, P53), enzymatic (superoxide dismutase [SOD]), and nonenzymatic oxidative stress (malondialdehyde [MDA]) tests. We found that pretreatment of AD in the rat model by M2000 had a potent efficacy on rat behavior and also it led to a significant inhibition of amyloid plaque production. Moreover, our data showed that M2000 can reduce the amount of Bax/Bcl2, P53, MDA, and SOD, as well as it normalized the level of procaspase-3. Our results suggest M2000 is a potential therapeutic agent for the treatment of AD.